The Legal Vacancy of Consumer Protection in Smart Contract Execution: A Substantive Justice Approach - Totok Catur Wismo Malaicanto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The Web3 digital economic transformation presents smart contracts that operate autonomously and decentralized based on the doctrine of